Clinical diagnosis of leptospirosis with negative serology: case series report - Mahmuda, Iin Novita Nurhidayati; Santi, Tika Melandya (International Journal of Health Science and Technology, 2023)
Leptospirosis is a zoonotic disease with clinical manifestations that range from mild acute febrile illness that resolves on its own to severe, life-threatening conditions with multiple organ dysfunction. Clinical features and various diagnostic tests establish leptospirosis diagnosis, such as bacterial isolation and serological examination. Because the antibody response required for serological testing is often insufficient to detect until the second week of disease (when the immune phase begins), sensitivity, when symptoms begin, is limited. Often, patients present with obvious clinical symptoms of leptospirosis but have negative serological test results. This study aimed to determine how to establish the clinical diagnosis of leptospirosis in leptospirosis cases with negative serology test results. This study used a descriptive method with a case series research design that analyzed four series of leptospirosis cases. The result of this study is that some cases of leptospirosis have obvious symptoms, but serological examination shows negative results. This can happen because new antibodies can be detected on day 6 to day 10 of the illness and reach their peak in 3-4 weeks so that the establishment of a clinical diagnosis of leptospirosis can be established from clear clinical symptoms and other laboratory tests. Establishing the clinical diagnosis of leptospirosis with negative serology can be done with the Faine scoring system.